COLLABORATION IN CREATING AN EDUCATIONAL CONSUMER JOURNEY: A MEANINGPERSPECTIVE FORMATION - Diah Fatma Sjoraida; Nyoman Dwika Ayu Amrita; Finny Redjeki (PT. Kreatif Indonesia Satu, 2024)
Collaboration in creating educational consumer journeys with a focus on creating meaning has become an increasingly important topic in modern marketing practice. This approach combines various experiential learning theories with interactive marketing strategies to produce immersive and meaningful consumer experiences. This study explores how the integration of these theories not only increases the relevance of marketing strategies, but also strengthens the relationship between brands and consumers through a holistic approach. The first subchapter discusses collaboration theory in marketing and consumer education, highlighting the importance of cross-disciplinary collaboration between academics, marketing practitioners, and information technology developers. The integration of these theories, such as the use of augmented reality (AR) and virtual reality (VR), allows consumers to interactively explore products or services in immersive simulated environments. The second subchapter explores the concept of meaning formation in consumer experience, emphasizing that consumer decision making is not only based on functional information, but also subjective interpretations of products or services. Collaboration between academics and marketing practitioners in guiding consumer experiences can strengthen understanding of the values and preferences held by consumers. In its conclusion, this study emphasizes that effective collaboration between academics, marketing practitioners and information technology developers is the key to increasing the relevance and effectiveness of marketing strategies in facing an increasingly dynamic global market. Marketing practitioners need to continue to develop communication strategies that are sensitive to diverse consumer values and preferences to build sustainable relationships. The integration of information technologies, such as AR and VR, drives more interactive and meaningful consumer experiences, while collaborative approaches to meaning creation deepen understanding of consumers' emotional and cognitive dynamics. Thus, collaboration in creating an educational consumer journey not only supports business growth, but also creates positive values for consumers in understanding and appreciating the brand more deeply.